2011
DOI: 10.3109/15368378.2011.596247
|View full text |Cite
|
Sign up to set email alerts
|

Selective destabilization of tumor cells with pulsed electric and magnetic sequences: a preliminary report

Abstract: These results have promising implications for the treatment of cancer and warrant further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…on the expression of circ-CDR1as, which can be attributed to the low time of continuous exposure. This has been confirmed in other studies (39). The activity of the PTEN gene in normal and tumor cells was also assayed at the various intensities of both continuous and discontinuous magnetic fields.…”
Section: Discussionsupporting
confidence: 79%
“…on the expression of circ-CDR1as, which can be attributed to the low time of continuous exposure. This has been confirmed in other studies (39). The activity of the PTEN gene in normal and tumor cells was also assayed at the various intensities of both continuous and discontinuous magnetic fields.…”
Section: Discussionsupporting
confidence: 79%
“…We focused on a breast cancer cell model given our previous success using PEMFs to slow their growth [8]. To ascertain the sensitivity of normal and cancer cells to PEMFs we exposed MCF7 breast cancer cells and their normal breast epithelial counterparts, MCF10s, to PEMFs of magnitudes between 2 mT and 5 mT and at a repetition rate of 20 Hz for 1h per day for three days.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by studies demonstrating the safety of very low frequency and intensity PEMFs [4], [6] and extending from our previous work [8], demonstrating that MCF7 cancer cells are selectively vulnerable to 20 Hz pulsed electromagnetic fields, we investigated the effects of PEMFs on human breast epithelial cells of malignant (MCF7) and non-malignant (MCF10) phenotypes. Cytotoxic sensitivity to certain PEMFs parameters was entirely restricted to the malignant phenotype and exhibited a clear dependency on the duration, frequency and intensity of the PEMFs employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that PEMF therapy may exert proliferative inhibition and mitotic spindle disruption [18,40], block the development of neovascularization required for tumor supply [46][47][48] and exacerbate an inherent or induced genetic instability by reducing the stringency of the late-cycle (G2) checkpoint [49]. While chemotherapy is not specific to cancer cells and targets all rapidly dividing cells [50][51][52], PEMFs exert selective cytotoxic effect on neoplastic cells [15,40,[53][54][55] making this therapy a highly promising strategy.…”
Section: In Vitro Studiesmentioning
confidence: 99%